The One-eyed Giant - Osborne, Mary Pope; Homer (New York : Hyperion Books for Children, 2002)
Retells a part of the Odyssey in which King Odysseus fights the cyclops.
Keywords: Odysseus (Greek mythology) -- Juvenile literature; Odysseus (Greek mythology); Mythology, Greek